Behavioral Treatment for Tension-Type Headache - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 2003)
The benefits of brief neurologist-administered behavioral treatment of pediatric episodic tension-type headache were determined at the University of West Florida, Pensacola, FL.